Voriconazole Induced Hallucinations and Visual Disturbances in a Female Child: A Case Report and Literature Review - Zheng, Rujiang; Li, Yu; Guo, Chuyi; Pei, Yuxin; Ke, Zhiyong; Huang, Libin (Frontiers in Pediatrics, 2021)
Voriconazole is a second-generation azole widely used for the prevention and treatment of fungal infection in leukemia patients. We report a case of 9-year-old girl with T-cell acute lymphoblastic leukaemia who developed hallucinations and visual disturbance after voriconazole treatment for twice. These symptoms began acutely after treatment with voriconazole and resolved rapidly when the voriconazole was stopped. No specific cause was identified, and thus the symptoms were considered to be the side effects of voriconazole. The hallucinations and visual disturbance caused by voriconazole in children have not been reported before and the causes of these side effects are unknown.